X-RAY EMISSION AND ORIENTATION OF SELECTED PF GALAXY CLUSTERS - Tugay, A. V.; Dylda, S. S.; Panko, E. A. (Одеські астрономічні публікації, 2016)
X-ray counterparts for 35 galaxy clusters contained in the PF catalogue of galaxy clusters and groups were found in XMM-Newton archive. 22 ones (all from ACO catalogue) have extended elliptic X-ray haloes appropriate for determination of orientation. Position angles and eccentricities were calculated and compared with cluster orientations optical band.